INVENTORY OF HERPETOFAUNA IN REGIONAL GERMPLASM PRESERVATION IN PULP AND PAPER INDUSTRY OGAN KOMERING ILIR REGENCY SOUTH SUMATRA - Noberio, Denny; Setiawan, Arum; Setiawan, Doni (BIOVALENTIA: Biological Research Journal, 2015)
The research aims to determine of herpetofauna in Regional Germplasm Preservation, PT. Bumi Mekar Hijau, Ogan Komering Ilir Regency, South Sumatra. The research was conducted in May until June 2015, conducted on 4 transect observation purposively determined by considering the type of habitat herpetofauna and the results of a preliminary survey. The method used in this research is the Visual Encounter Survey (VES). Observations carried out in the morning and evening. The total number of herpetofauna were found during the observation as many as 15 species of 9 families. The number of amphibians was found as many as 6 species of 3 families and reptiles as many as 9 species of 6 families. There are two species categorized as Vulnerable in IUCN 2015 and Appendix II CITES which are the Siebenrockiella crassicollis and Cuora amboinensis cuoroÂ Keywords : Inventory, herpetofauna, regional germplasm preservation, industrial plantation forest